Smart Attendance: Automated Face Recognition System During Final Examination in UTP - Paramasivam, Puniswary (IRC, 2019)
Smart Attendance is a user-friendly face recognition system that is planned to be developed in order to replace the current traditional method of recording attendance of students in UTP during Final Examination. This report focuses on the scope of the project entirely and how it is aimed to be developed for the purpose of bringing out a system that can be useful for UTP students, lecturers as well as for Examination Unit. There are various issues that can be derived from current manual method where it is found to be less efficient and effective. Problems are highly related to the database updates and the time and paper consumption which eventually ends in a slow process of completing the attendance record for the entire examination hall. This project is planned to be designed using Agile methodology. Besides, feature extraction of students’ face is expected to utilize the machine learning in order to ease the development process. In addition, knowledge on required algorithm are described on this report too. As per the requirement gathering phase, interviews of the staffs from Examination Unit as well as surveys for the UTP students and lecturers are conducted to obtain the feedback and the perspectives on this system. The result of the interview and survey have proven the need to replace the current manual method of recording attendance of students during Final Examination for the betterment of Examination Unit of UTP.